2018
DOI: 10.1002/hrdq.21333
|View full text |Cite
|
Sign up to set email alerts
|

Noe, R. (2017). Employee training and development. New York, NY: McGraw Hill Education. ISBN: 978‐0078112850

Abstract: The seventh edition of the book, Employee Training and Development by Robert Noe, provides an in-depth analysis of the components of training for human resource (HR) professionals. Noe's text examines four major areas: context for training and development, designing training, training methods, and the future of the profession (2017). Compared to previous editions, this text offers a more in-depth and up-to-date analysis of advancements in the HR development field including strategic planning and technological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 1 publication
0
9
0
1
Order By: Relevance
“…The term hydrochemical facies is a function of solution kinetics, rock-water interactions, geology, and pollution sources used to describe water quantities that differ in their chemical composition [1]. This can be clearly represented by drawing the Piper trilinear diagram [59], which is useful for geochemical evaluation among groundwater samples in more definite terms rather than with other possible plotting methods [60]. The Piper diagram consists of two triangle fields indicating the percentage distribution for the major ions to determine the hydrochemical facies of the groundwater [61].…”
Section: Resultsmentioning
confidence: 99%
“…The term hydrochemical facies is a function of solution kinetics, rock-water interactions, geology, and pollution sources used to describe water quantities that differ in their chemical composition [1]. This can be clearly represented by drawing the Piper trilinear diagram [59], which is useful for geochemical evaluation among groundwater samples in more definite terms rather than with other possible plotting methods [60]. The Piper diagram consists of two triangle fields indicating the percentage distribution for the major ions to determine the hydrochemical facies of the groundwater [61].…”
Section: Resultsmentioning
confidence: 99%
“…Specific training can also deepen the organization's understanding by employees who participate in the training, leading them to quickly identify with the organization (Noe & Kodwani, 2018). When employees find that KSAs acquired through firm-specific training can be fully applied to their current work, the human capital acquisition is more likely to be embedded in the current job or organization (Barth, 1997;Lazear, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Much evidence shows many firms are willing to increase human resources investment through the various employee training and development programs (Guan & Frenkel, 2019). Employee training is defined as the training activity planned and targeted in various ways based on the organization's actual work needs (Noe & Kodwani, 2018). Scholars have confirmed that training could improve economic performance and non-economic performance, including reducing turnover, absence, conflicts, and service quality by improving employees' knowledge, abilities, skills (KSAs, hereafter), and behaviors (Phillips, 2012;Guan & Frenkel, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One such therapy, foot reflexology, uses a firm thumb-walking motion to apply pressure to areas of the feet called reflexes. It is based on the theory that foot reflexes are related to specific organs, glands, and systems of the body, and that targeting these reflexes helps to restore balance to the body (Watson & Voner, 2008). …”
Section: Dyadic Recruitment In Complementary Therapy Studies: Experiementioning
confidence: 99%